COMPARATIVE ANALYSIS OF THE USE OF CHROMEBOOK MEDIA AND SERIAL IMAGE MEDIA ON IMPROVING THE ABILITY TO UNDERSTAND FICTIONAL STORIES OF GRADE V STUDENTS OF SD NEGERI 122 LAMBALE, EAST KABAENA DISTRICT, BOMBANA REGENCY - liasmin, Liasmin; Siti Suwadah Rimang; Paida, Andi (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to describe the implementation of the deep learning approach in Indonesian language learning and its impact on the development of critical and reflective thinking skills of high school students in several schools in Makassar City. The deep learning approach is seen as an innovative learning strategy that emphasizes high-level thinking processes, active engagement, and deep reflection on teaching materials. The research method used is descriptive qualitative with data collection techniques through observation of learning activities, interviews with teachers and students, and analysis of learning outcome documents. The results of the study show that the application of the deep learning approach contributes positively to improving the quality of learning interactions and students' metacognitive awareness. Students show high ability to identify problems, analyze arguments, draw logical conclusions, and reflect on the learning process. Deep learning-based learning also strengthens collaborative interaction patterns in the classroom and encourages students' intellectual independence. Thus, the deep learning approach is relevant to be applied in Indonesian language learning in high school to foster critical, reflective, and literacy skills in accordance with the demands of 21st century education.